2017
DOI: 10.21873/anticanres.11465
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression Confers Better Prognosis in Locally Advanced Oral Squamous Cell Carcinoma

Abstract: PD-L1 expression was associated with CD8 tumor-infiltrating lymphocytes and better outcome in patients with LAOSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 21 publications
1
33
1
Order By: Relevance
“…Coincidentally, Loeser's study 6 showed the same trend in esophageal adenocarcinoma. Moreover, we found the same trends not only in the studies of VISTA, but also in some studies of other negative immune molecules, such as PD-1 and PD-L1 [15][16][17][18][19][20] . Badoua showed that PD-1 + TILs were associated with favourable OS in human papillomavirus(+) head and neck cancer.…”
Section: Discussionsupporting
confidence: 80%
“…Coincidentally, Loeser's study 6 showed the same trend in esophageal adenocarcinoma. Moreover, we found the same trends not only in the studies of VISTA, but also in some studies of other negative immune molecules, such as PD-1 and PD-L1 [15][16][17][18][19][20] . Badoua showed that PD-1 + TILs were associated with favourable OS in human papillomavirus(+) head and neck cancer.…”
Section: Discussionsupporting
confidence: 80%
“…After screening the title and abstract, 112 studies were excluded for their irrelevance to the topic. Finally, we included 16 studies after reviewing the full texts (1124, 33, 34). Studies were excluded for the following reasons: six had no information about OS/DFS/PFS or reported no clinicopathological data; six had insufficient data for quantitative analysis; and two were reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Some evidence supports that high PD-L2 expression in cancer specimens predicts impaired survival for various solid tumors (1216). Nevertheless, several studies report negative results or even opposing findings (11, 1724). Therefore, we assessed the consistency and magnitude of the prognostic effect of PD-L2 in solid cancer patients after surgery through a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study, higher expression of PD-L1 tended to be associated with better OS. Kogashiwa et al [35] found that higher expression of PD-L1 was associated with a higher number of CD8+ tumor-infiltrating lymphocytes, leading to better OS for HNC patients. Balermapas et al and Hanna et al [36,37] also reported higher levels of tumor-infiltrating lymphocytes in HNC patients expressing higher levels of PD-L1, which could explain the improved OS of these patients.…”
Section: Discussionmentioning
confidence: 99%